Epimeria (Pseudepimeria) callista d'Acoz & Verheye 2017, sp. nov. - d'Acoz, Cédric d'Udekem; Verheye, Marie L. (Zenodo, 2017)
Epimeria ( Pseudepimeria ) callista sp. nov. urn:lsid:zoobank.org:act: 8E717EF2-0CC3-4796-859D-90F60B661961 Figs 257–264 Epimeria grandirostris – Bellan-Santini, 1972: 223. ‘Clade H grandirostris-pulchra-oxicarinata complex - GR2ʹ – Verheye et al. 2016a, supplement: 5 (online). non Pseudepimeria grandirostris Chevreux, 1912: 216. Etymology From the Greek, καλλιστος, Latinized as callistus , -a , -um , adjective meaning very beautiful, the most beautiful. Type material Holotype RV Aurora Australis cruises: SOUTHERN OCEAN: adult ♀, cruise CEAMARC, sample CEAMARC 3978, stn 36EV297, Adélie Coast, 66°20ʹ20″ S, 143°41ʹ08″ E, 552–573 m, beam trawl, 4 Jan. 2008, coll. IPEV-AAD-MNHN (MNHN-IU-2014-7336, removed from MNHN-IU-2014-4327) [Extraction P40; Genbank nr, 28S: KU759683]. Paratypes RV Aurora Australis cruises: SOUTHERN OCEAN: 1 dissected adult ♀, cruise CEAMARC, sample CEAMARC 3978, stn 36EV297, Adélie Coast, 66°20ʹ20″ S, 143°41ʹ08″ E, 552–573 m, beam trawl, 4 Jan. 2008, coll. IPEV-AAD-MNHN, (MNHN-IU-2014-7337, removed from MNHN-IU-2014-4327). RV Seatruck cruises: SOUTHERN OCEAN: 1 small and damaged spec., cruise REVOLTA II, stn REVO_029, Collect_ID: REVO_183, Adélie Coast, 66°39ʹ30″ S, 140°01ʹ59″ E, 97–103 m, beam trawl, 26 Jan. 2011, coll. N. Améziane, N. Bax, C. Gallut, A.C. Lautrédou and C. Robineau (MNHN-IU-2014-4300). Description ROSTRUM. Long, overreaching tip of peduncle of antenna 1; in lateral view, regularly curved along all its length, not forming an angle with head, ventrally straight, tip not abruptly curving downwards; in frontal view, fairly narrow, with weakly convex borders, with acute tip. EYE. Medium-sized, conical. PEREION–PLEOSOME TOOTH PATTERN. Pereionite 1 with low, very broad, rounded mid-dorsal tooth of which the anterior border is very oblique, with pair of well-developed, rounded, dorsolateral teeth and pair of small ventrolateral teeth; pereionite 2 much narrower than pereionites 1 and 3, with small broad rounded tooth pointing upwards (as high as mid-dorsal tooth of pereionite 1 and distinctly shorter than middorsal tooth of pereionite 3), with pair of very small dorsolateral teeth, and pair of small ventrolateral teeth; pereionite 3 with medium-sized, broad and rounded mid-dorsal tooth of which the anterior and the posterior borders are both strongly convex, with pair of medium-sized, low and blunt dorsolateral teeth, and pair of small ventrolateral teeth; pereionites 4–7 with fairly large and broad mid-dorsal tooth pointing upwards, of which the anterior border is strongly convex and the posterior border nearly straight, and of which the tip is bluntly angulate, and with pair of medium-sized, low and blunt dorsolateral teeth, and pair of small ventrolateral teeth; pleonites 1–2 with large and broad mid-dorsal tooth pointing upwards, of which the anterior border is strongly and regularly convex and the posterior border straight, and of which the tip is subacute, and with pair of large subacute dorsolateral teeth and 4 pairs of much smaller denticles; pleonite 3 with medium-sized, fairly broad, triangular mid-dorsal tooth pointing upwards, of which the anterior border is proximally convex, medially concave and distally straight, the tip subacute and the posterior border nearly straight, with 5 pairs of dorsolateral teeth. COXAE 1–3. Strongly carinate and distally sharp. COXA 4. Anterodorsal border nearly straight; anteroventral border with proximal very shallow concavity, with distal part distinctly convex; anterior angle very broadly rounded and slightly projecting forward; ventral tooth long, broad and subacute, directed backwards; lateral carina with broadly rounded lobe distinctly projecting laterally, posteriorly followed by fairly deep rounded concavity and small extremely low second lobe; in lateral view, inner corner of carina forming a distinct squared angle; in lateral view posteroventral border of coxa deeply concave; the concavity is rounded, not distinctly angulate. COXA 5. In dorsal view, with medium-sized, triangular, carinate, lateral tooth, of which the anterior border points weakly obliquely backwards and the posterior border is nearly perpendicular to body axis; tip of carina broadly rounded. COXA 6. With triangular carinate lateral tooth of which the anterior border points obliquely backwards and the posterior border is nearly perpendicular to body (character to be examined in dorsal view); tip of carina subacute. COXA 7. With ventral + posterior borders forming a regular curve, with small lateral tooth. EPIMERAL PLATES 1–3. Plate 1 with posteroventral angle angulate, with distinct lateral carina and 2 lateral teeth; plate 2 with posteroventral angle sharply angulate (forming a distinct blunt-tipped tooth in squared angle), with distinct lateral carina and 2 lateral teeth; plate 3 with posteroventral angle produced into a fairly long tooth, with distinct lateral carina and 1 lateral tooth, with posterior margin weakly convex. UROSOME TOOTH PATTERN. Urosomite 1 with sharp narrow tooth pointing upwards, not anteriorly preceded by pair of denticles; urosomite 2 with pair of tiny posterior dorsolateral teeth pointing upwards; urosomite 3 with pair of mid-sized posterior dorsolateral teeth pointing upwards. TELSON. Cleft on 0.35; tips of lobes rounded, notch forming a fairly narrow slit. PEDUNCLE OF ANTENNA 1. Article 1 with anterior border weakly concave, with trace of anterior and posterior tooth; article 2 with medium-sized lateral triangular tooth; article 3 with weak ventral tooth. GNATHOPODS 1–2. Very small, achelate; carpus and propodus of normal slenderness in gnathopod 1 (propodus tapering), extremely narrow in gnathopod 2; dactylus of gnathopod 2 very broad and posteriorly strongly convex. PEREIOPODS 3–4. Merus, carpus and propodus extremely broad and short; dactylus fairly large, strongly curved on both sides, clasping. PEREIOPOD 5. Basis of normal width, with posteroproximal process rounded and strongly protruding, with posterodistal tooth fairly strong, triangular and sharp; merus, carpus and propodus extremely broad and short; dactylus fairly large, strongly curved on both sides, clasping. PEREIOPOD 6. Basis of normal width, with posteroproximal process acutely triangular, with posterodistal tooth strong, narrow and sharp; merus, carpus and propodus extremely broad and short; dactylus fairly large, strongly curved on both sides, clasping. PEREIOPOD 7. Basis broad; posterior border distinctly diverging from axis of basis in proximal 0.75; at this level it forms a distinct nearly squared (very slightly obtuse) angle, which is followed by a deep concavity; this concavity forms a broadly rounded curve; the posterodistal corner is produced into a long narrow tooth pointing obliquely backwards. Body length Up to 22 mm. Distribution Adélie Coast, 97– 573 m. Remarks Epimeria callista sp. nov. (Adélie Coast) is very similar to E. kharieis sp. nov. (eastern shelf of the Weddell Sea) and E. grandirostris (Antarctic Peninsula and surrounding islands). Molecular phylogenetic analysis of 28S rDNA (Verheye et al. 2016a) supports the species status of E. callista sp. nov. and E. grandirostris. Epimeria kharieis sp. nov. is herein recognized as a distinct species based on morphology alone, as the type material was not suitable for genetic studies. See key of the subgenus Pseudepimeria for differences between the three species. Allometric differences have been observed in immatures and juveniles of these species, therefore the morphological characters given in the key and descriptions refer to adult females only. : Published as part of d'Acoz, Cédric d'Udekem & Verheye, Marie L., 2017, Epimeria of the Southern Ocean with notes on their relatives (Crustacea, Amphipoda, Eusiroidea), pp. 1-553 in European Journal of Taxonomy 359 on pages 124-126, DOI: 10.5852/ejt.2017.359, http://zenodo.org/record/3855694 : {"references": ["Bellan-Santini D. 1972. Invertebres marins des XIIeme et XVeme Expeditions Antarctiques Francaises en Terre Adelie. 10. Amphipodes Gammariens. Tethys, Supplement 4: 157 - 238.", "Verheye M., Backeljau T. & d'Udekem d'Acoz C. 2016 a. Looking beneath the tip of the iceberg: diversification of the genus Epimeria on the Antarctic shelf (Crustacea, Amphipoda). In: Gutt J., David B. & Isla E. (eds) High environmental variability and steep biological gradients in the waters off the northern Antarctic Peninsula. Polar Biology 39 (5): 925 - 945, online supplementary material https: // doi. org / 10.1007 / s 00300 - 016 - 1910 - 5", "Chevreux E. 1912. Deuxieme expedition dans l'Antarctique, dirigee par le Dr. Charcot. 1908 - 1910. Diagnoses d'amphipodes nouveaux. Bulletin du Museum national d'Histoire naturelle, Paris 18 (4): 208 - 218 (1 - 12 on reprints). http: // biodiversitylibrary. org / page / 34142291 [accessed 27 Sep. 2016]."]}